Global southern limit of flowering plants and moss peat accumulation - Convey, Peter; Hopkins, David W; Roberts, Stephen J; Tyler, Andrew N (Polar Research, 2011)
The ecosystems of the western Antarctic Peninsula, experiencing amongst the most rapid trends of regional climate warming worldwide, are important “early warning” indicators for responses expected in more complex systems elsewhere. Central among responses attributed to this regional warming are widely reported population and range expansions of the two native Antarctic flowering plants, Deschampsia antarctica and Colobanthus quitensis. However, confirmation of the predictions of range expansion requires baseline knowledge of species distributions. We report a significant southwards and westwards extension of the known natural distributions of both plant species in this region, along with several range extensions in an unusual moss community, based on new survey work in a previously unexamined and un-named low altitude peninsula at 69º22.0’S 71º50.7’W in Lazarev Bay, north-west Alexander Island, southern Antarctic Peninsula. These plant species therefore have a significantly larger natural range in the Antarctic than previously thought. This site provides a potentially important monitoring location near the southern boundary of the region currently demonstrated to be under the influence of rapidly changing climate trends. Combined radiocarbon and lead isotope radiometric dating suggests that this location was most likely deglaciated sufficiently to allow peat to start accumulating towards the end of the 19th century, which we tentatively link to a phase of post-1870 climate amelioration. We conclude that the establishment of vegetation in this location is unlikely to be linked to the rapid regional warming trends recorded along the Antarctic Peninsula since the mid-20th century. Antarctic plants, distribution limits, peat accumulation, dating.
Keywords: Antarktis; hårgress; klimaendringer; perleurt; planter; økosystemer

Colonization and demographic structure of Deschampsia antarctica and Colobanthus quitensis along an altitudinal gradient on Livingston Island, South Shetland Islands, Antarctica - Vera, María Luisa (Polar Research, 2011)
The colonization capacity and demographic structure of populations of Deschampsia antarctica and Colobanthus quitensis were studied in different microhabitats between 10 and 147 m a.s.l. on Livingston Island, South Shetland Islands, near the Spanish Antarctic base Juan Carlos I, in February 2002. At the highest site (147 m a.s.l.), mean temperatures were about 1 ºC lower than at sea level. Both species are less common in inland areas and at the highest altitudes only occur at restricted sites that are frequently snow-free in the early austral summer. The diameters of the largest plants (C. quitensis cushions 7-8 cm ; D. antarctica tufts 10-11 cm) in the populations growing at the highest altitudes (110 and 147 m a.s.l.) suggest that these populations were established about 24-28 years ago. The largest diameter plants (Deschampsia 20 cm; Colobanthus 18 cm) were found at the lowest altitudes on deep soil. The presence of numerous seedlings and young individuals on the periphery of populations established several years ago or at recently colonized sites suggests an active process of expansion. There were more emerged seedlings of C. quitensis than of D. antarctica, but the density of established individuals was higher for D. antarctica, suggesting these species have different demographic strategies. Keywords: Antarctic vascular plants; altitude and habitat effect; colonization; population structure.
Keywords: Antarktis; biologi; flora; planter